Asymmetric Impact of World Oil Prices on Marketing Margins: Application of NARDL Model for the Indonesian Coffee - Kamaruddin, Kamaruddin; Hazmi, Yusri; Masbar, Raja; Syahnur, Sofyan; Majid, M. Shabri Abd. (International Journal of Energy Economics and Policy, 2021)
The World oil prices shocks is believed become the main important role to movements marketing margins of agricultural commodities, include coffee. We aim to investigate the impact of world oil prices shocks on coffee marketing margins for Indonesia. We decompose world oil prices into positive and negative shocks to investigate the asymmetric impacts on marketing margins. For this aims, we adopt a NARDL model to capture the asymmetric impacts both in long and short run. We found that a decrease in oil price has a positive and significant impact on marketing margins, while a decrease in oil price has a significant negative impact. An increase in world oil prices lead to reduce marketing margins. Similarly, a decrease in world oil prices, also impact on the reduction of marketing margins. We therefore conclude that impacts of world oil prices shocks on marketing margins not only asymmetric in magnitude but also in direction. Particularly, the result of the NARDL estimation reveal that negative shock in oil prices has more pronounced impact than positive shocks on the reduction of marketing margin. This result implies that Indonesian coffee producers more benefit when the world oil price decreases compare than increases. Keywords: Oil prices, marketing margin, coffee producers and NARDL model JEL Classifications: C32, F13, F43, G13. DOI: https://doi.org/10.32479/ijeep.11857